Ավանդույթի գործառույթը անձի արժեհամակարգի ձևավորման համատեքստում - Աղավնի Քոլյան (ՀՀ ԳԱԱ հրատ.)
В статье представлена роль традиций и их значение в контексте становления ценностей личности. Представляются основные функции традиций, которые выделяются в значимых общественных нормах, в поведении личности с целью ее сохранения. The article presents the role and significance of tradition in the context of values formation. It also presents the main functions of traditions which are allocated in the significant social norms in the behavior of the individual with the purpose of its preservation.
Keywords: Psychology; Manners and customs